ASSOCIATION BETWEEN AEROBIC FITNESS AND CARDIOVASCULAR RISK FACTORS IN CHILDREN (Fiep Bulletin - online, 2013)
Objective: to identify the association of aerobic fitness with cardiovascular disease risk factors in children. Methods: cross-sectional study with 290 school children of 6 to 10 years old of both sexes, randomly selected. The aerobic fitness was assessed by the 20 meters shuttlle run test (Yo-Yo test).Blood was collected after a 12-hour fasting period. Blood pressure, stature and weight were evaluated in accordance with international standards. As cardiovascular risk factors, it was considered: body mass index (BMI), systolic and diastolic blood pressure (SBP or DBP), HDL and LDL cholesterol, triglycerides and insulin levels. Spearman's coefficient was used to identify the association between the variables. Results: significant inverse correlations were found, in both sexes, among aerobic fitness and BMI, DBP, triglycerides and insulin levels. Significant inverse correlations were found, only in boys, among aerobic fitness and PAS and LDL cholesterol. Conclusion: the significant associations among aerobic fitness and cardiovascular risk factors in children justify the use of these variables in monitoring the health in pediatrics.
Keywords: children; cardiovascular risk; aerobic fitness